Reusing waste biomass in crop protection—Calcinated oyster shell powder enhances rhizospheric microbial-mediated suppression of root-knot nematodes - Jiang, Qipeng; Yu, Jiamin; Wang, Yong; Wang, Jinfeng; Jiang, Lianqiang; Guo, Shiping; Qian, Yu; Yu, Xiangwen; Liu, Dongyang; Xi, Daojiang; Deng, Quan; Ding, Wei; et al. (Frontiers in Microbiology, 2025)
Root-knot nematodes (RKNs), particularly Meloidogyne incognita, are one of the most destructive plant-parasitic nematodes (PPNs) affecting crop production worldwide. Previous earlier study revealed that calcinated oyster shell powder (OSP) possessed excellent suppression of tobacco RKN disease. However, the suppression mechanism of OSP against RKNs still remains unrevealed. Hence, this study aimed to clarify the suppression mechanism of oyster shell powder against RKNs by pot experiments and high-throughput sequencing. The results showed that calcinated OSP reduced over 38% of the tobacco root-knot index by inhibiting the migration of second-stage juveniles of Meloidogyne incognita (J2) in soil. Furthermore, calcinated OSP reduced J2 density by 43.69% in the tobacco rhizosphere, and significantly increased soil pH by 0.68; moreover, it increased the contents of soil exchangeable calcium (ExchCa) and exchangeable magnesium (ExchMg) by over 50%. Meanwhile, soil properties, including ExchMg, ExchCa, and pH, enhanced microbial-mediated suppression of J2. Specifically, some taxa within Proteobacteria- and Gemmatimonadota-dominated microbial communities and fungal richness may contribute to suppression of RKNs. Conversely, some taxa within Chloroflexi- and Acidobacteriota-dominated microbial communities may be involved in RKNs' prosperity. Our study suggests that reusing waste oyster shell powder as an innovative antagonist against RKNs presents promising avenues for nature-based PPN management strategies, and would generate significant economic value and social impact in plant protection.